2012
DOI: 10.1093/humrep/des297
|View full text |Cite
|
Sign up to set email alerts
|

Decorin is a part of the ovarian extracellular matrix in primates and may act as a signaling molecule

Abstract: This study was supported by Deutsche Forschungsgemeinschaft (DFG) MA1080/17-3 and in part DFG MA1080/21-1 (to AM), NIH grants HD24870 (S.R.O. and R.L.S.), the Eunice Kennedy Shriver NICHD/NIH through cooperative agreement HD18185 as part of the Specialized Cooperative Centers Program in Reproduction and Infertility Research (S.R.O.) and 8P51OD011092-53 for the operation of the Oregon National Primate Research Center (G.A.D., J.D.H., S.R.O. and R.L.S).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Amplified PCR products were separated and visualized by ethidium bromide stained agarose gels. The identities of all PCR products were verified by sequencing [30, 35]. For primer sequence information, please see Table 3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amplified PCR products were separated and visualized by ethidium bromide stained agarose gels. The identities of all PCR products were verified by sequencing [30, 35]. For primer sequence information, please see Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…The activities of the effector caspases 3/7 were determined following exposure of human GCs to proNGF and NGF [34, 35]. Cells were cultured for 2 days, seeded on white walled 96-well plates (20000 cells per well) and then treated with different concentrations of proNGF and NGF for 24 h. Staurosporine (1 μM; Sigma-Aldrich) was used as positive control.…”
Section: Methodsmentioning
confidence: 99%
“…Using immunohistochemistry in adult rhesus monkey and human ovaries, it was found that DCN is expressed in theca cells, the corpus luteum (CL), and follicular fluid (FF) [13] Moreover, it was shown that adding DCN to cultured CGs, elevated intracellular Ca2+ levels and phosphorylation of EGFR. Based on these results the study suggested that DCN plays multiple roles in granulosa cells, including folliculogenesis, ovulation, and survival of the CL [14]. More recent work demonstrated that DCN regulates apoptosis and cell cycle of granulosa cells in goat ovaries [15].…”
Section: Introductionmentioning
confidence: 87%
“…Specific ECM molecules, including the multi-adhesive basement membrane protein fibronectin (FN) and a small leucine-rich proteoglycan decorin (DCN), are required for folliculogenesis and ovulation (Adam et al, 2012;Yasuda et al, 2005). In a previous study, we have demonstrated that DCN, a differentially expressed gene, was screened from ovarian tissues between polytocous and monotocous dairy goats by suppressive subtractive hybridization (Zhu et al, unpublished data).…”
mentioning
confidence: 99%
“…The binding causes phosphorylation and activation of EGFR and can be followed by downregulation of EGFR signaling, resulting in a long-term blockage of EGF/EGFR actions (Adam et al, 2011;Csordas et al, 2000). Adam et al (2012) furthermore indicated that the EGFR is one of the growth factor receptors directly targeted by DCN in human GCs and DCN is a local regulator of folliculogenesis, ovulation and the functional lifespan of the CL in primates. Recent studies demonstrated that the expression of FN was elevated in the superstimulation group and its expression was reported to be inversely related to follicle maturation (Berkholtz et al, 2006;Dias et al, 2013;Yasuda et al, 2005).…”
mentioning
confidence: 99%